US exceptionalism and UK localism? Cross-border insolvency law in comparative perspective. (2nd January 2018) - McCormack, Gerard
Abstract : This paper addresses how the UNCITRAL Model Law on Cross-Border Insolvency has been implemented and interpreted in the US and the UK. The Model Law has attained a measure of international acceptance and is intended to achieve greater efficiencies in the administration of insolvency cases with transnational dimensions. But different manners of implementation in different countries and differing interpretations may hinder the prospects for harmonisation and coordination of laws. The paper will address in particular whether US interpretations differ from those in the UK and whether the US decisions are so infused with 'American exceptionalism' that they cannot be relied upon as sure guides in other countries.